Pengaruh Self-Leadership, Perceived Organizational Support, Proactive Personality, Supervisor Support terhadap Work Engagement pada PT.Sinar Sosro Cabang Bekasi - Kiki Fadilah; Justine Tanuwijaya (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
This study aims to analyze the effect of self-leadership, perceived organizational support, proactive personality, supervisor on work engagement in employees of PT Sinar Sosro Bekasi Branch. This research is quantitative research by distributing questionnaires. This research uses purposive sampling testing method. Hypothesis testing using multiple regression analysis with SPSS software. The data in this study were collected from 120 employees of PT Sinar Sosro Bekasi Branch. The results show that self-leadership, perceived organizational support, proactive personality, supervisor support have a positive effect on work engagement.